Hierarchical porous carbon derived from green cyclodextrin metal‐organic framework and its application in microwave absorption - Zhang, Shao‐Xia; Xu, Long; Chen, Zhi‐Hui; Fan, Shu‐Ting; Qiu, Zhen‐Jiang; Nie, Zi‐Jun; Li, Bang‐Jing; Zhang, Sheng (Journal of applied polymer science, 2021)
γ‐cyclodextrin (CD)‐metal‐organic framework (MOF)‐K is developed as a new kind of green template for the preparation of hierarchical porous carbon (HPC). Three‐level porous structure (micro‐, meso‐, and macro‐pores) has been successful constructed by calcined γ‐CD‐MOF‐K at 600°C. The fabricated carbon (HPC‐600) shows good microwave adsorption ability due to its unique hierarchical porous structure (macropores allow microwave enter the interior of the absorbents, and then micro‐ and meso‐pores attenuate the incident microwave effectively by multiple reflections and polarization loss caused.) The minimum reflection loss (RL) is − 23.5 dB and the effective absorption bandwidth (EAB, RL≤− 10 dB) is 4.3 GHz. This work provides a good reference for efficient and environment‐friendly microwave absorbents. In addition, the applications of HPC‐600 may further expand to adsorption, sensing and supercapacitors due to the hierarchically porous structure. γ‐CD‐MOF‐K was prepared by ultrasonic method and calcined at 600°C to construct three‐stage porous structure HPC‐600. Because of its hierarchical porous structure, it has good microwave adsorption capacity (the macropores allow microwave to enter the absorber, and the micropores and mesopores effectively attenuate the incident microwave through multiple reflection and polarization loss).